2013
DOI: 10.1039/c3cp50416f
|View full text |Cite
|
Sign up to set email alerts
|

In situ/operando studies for the production of hydrogen through the water-gas shift on metal oxide catalysts

Abstract: In this perspective article, we show how a series of in situ techniques {X-ray diffraction (XRD), pair-distribution-function analysis (PDF), X-ray absorption fine structure (XAFS), environmental transmission electron microscopy (ETEM), infrared spectroscopy (IR), ambient-pressure X-ray photoelectron spectroscopy (AP-XPS)} can be combined to perform detailed studies of the structural, electronic and chemical properties of metal oxide catalysts used for the production of hydrogen through the water-gas shift reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 116 publications
(465 reference statements)
4
85
1
Order By: Relevance
“…A significant enhancement of the water splitting process on partially reduced ceria has been already reported [38,[54][55][56][57].Recently, Anarifard et al [53] found for Pt/CeO2…”
mentioning
confidence: 83%
“…A significant enhancement of the water splitting process on partially reduced ceria has been already reported [38,[54][55][56][57].Recently, Anarifard et al [53] found for Pt/CeO2…”
mentioning
confidence: 83%
“…Their studies aim to obtain a systematic understanding of the structural, electronic, and chemical properties of these catalysts under the operando conditions, in order to reveal the nature of the active phase in metal/oxide WGS catalysts and the WGS reaction mechanism. Some of these studies have been reviewed in subsection of "Oxide nanoparticles" in this paper, and interested readers are referred to a few review articles [108,109] on the capabilities, challenges, and opportunities of the in-situ/operando catalytic studies.…”
Section: Reviewsmentioning
confidence: 99%
“…Water dissociation was found to be the rate-limiting step and the authors suggested that the reduced ceria support facilities H 2 O dissociation. Following this line, the authors performed extensive work on oxidesupported metals to show the importance of the metal-support interface in the WGS reaction [76]. It is worthwhile to mention that for Cu {111}, Gokhale et al explored the same mechanism, except for the COOH dissociation step: instead of direct dissociation of H to the Cu surface, COOH dissociates H to a OH surface intermediate [77].…”
Section: Computational Studies On Wgs By Au/ceomentioning
confidence: 96%
“…This will generate a surface oxygen vacancy neighboring to Au. Such oxygen vacancy between the Au adatom and ceria surface plays an important role in the water activation step [76,80]. Water adsorbs at the interface between Au and the defective ceria surface with an adsorption energy of 61 kJ mol −1 (Figure 19) [81].…”
Section: Computational Studies On Wgs By Au/ceomentioning
confidence: 99%